Characterization of horizontal air–water two-phase flow in a round pipe part II: Measurement of local two-phase parameters in bubbly flow. (November 2015) - Talley, Justin D.; Worosz, Ted; Kim, Seungjin
Highlights: Measured local two-phase flow parameters in horizontal air–water bubbly flow. Lateral distributions of two-phase flow parameters are not uniform. Turbulence can promote the profiles to become more uniform with axial development. Void-weighted slip ratio approaches unity with increasing jf . One-dimensional transport highlights cases where bubble interactions are dominant. Abstract: The current work seeks to develop an additional database in air–water horizontal bubbly flow through a 3.81 cm inner diameter test section with a total development length of approximately 250 diameters. The experimental conditions are chosen to cover a wide range of the bubbly flow regime based upon flow visualization using a high-speed video camera. A database of local time-averaged void fraction, bubble velocity, interfacial area concentration, and bubble Sauter mean diameter are acquired throughout the entire pipe cross-section using a four-sensor conductivity probe for nine flow conditions. To investigate the evolution of the flow, measurements are made at axial locations of 44, 116, and 244 diameters downstream of the inlet. Using this database, the effects of gas flow rate, liquid flow rate, and development length on the local and area-averaged two-phase flow parameters are presented. From the local profiles, it is found that highly turbulent liquid flow conditions cause the void fraction profile to become more uniform with increasing development length through a turbulent mixing process which counters the effect of buoyancy. Bubble interactions are also observed to play a significant role in the evolution of the flow such that the area-averaged void fraction and interfacial area concentration can have different axial trends.